Minimum clinically important difference in Quantitative Lung Fibrosis score associated with all-cause mortality in idiopathic pulmonary fibrosis: subanalysis from two phase II trials of pamrevlumab - Matthew S Brown; Jonathan Goldin; Grace Hyun Kim; Xueping Zhang; Lona Poole (BMJ Open)
Objectives Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease. Chest high-resolution CT (HRCT) is instrumental in IPF management, and the Quantitative Lung Fibrosis (QLF) score is a computer-assisted metric for quantifying lung disease using HRCT. This study aimed to assess the change in QLF score associated with a minimum clinically important difference (MCID) of IPF symptoms and physiological lung function, and also determine the MCID of QLF change associated with all-cause mortality to serve as an imaging biomarker to confirm disease progression and response to therapy.Design and study setting We conducted post hoc analyses of prospective data from two IPF phase II studies of pamrevlumab, a fully human monoclonal antibody that binds to and inhibits connective tissue growth factor activity.Participants Overall, 152 patients with follow-up visits after week 24.Methods We used the anchor-based Jaeschke’s method to estimate the MCID of the QLF score that corresponded with the already established MCID of St. George’s Respiratory Questionnaire (SGRQ) and percent-predicted forced vital capacity (ppFVC). We also conducted a Cox regression analysis to establish a sensitive and robust MCID of the QLF score in predicting all-cause mortality.Results QLF changes of 4.4% and 3.6% corresponded to the established MCID of a 5-point increase in SGRQ and a 3.4% reduction in ppFVC, respectively. QLF changes of 1% (HR=4.98, p=0.05), 2% (HR=4.04, p=0.041), 20 mL (HR=6.37, p=0.024) and 22 mL (HR=6.38, p=0.024) predicted mortality.Conclusion A conservative metric of 2% can be used as the MCID of QLF for predicting all-cause mortality. This may be considered in IPF trials in which the degree of structural fibrosis assessed via HRCT is an endpoint. The MCID of SGRQ and FVC corresponds with a greater amount of QLF and may reflect that a greater amount of change in fibrosis is required before there is functional change.Trial registration number NCT01262001, NCT01890265.